Possible structural transformation and enhanced magnetic fluctuations in exfoliated α-RuCl3. (May 2019) - Zhou, Boyi; Wang, Yiping; Osterhoudt, Gavin B.; Lampen-Kelley, Paula; Mandrus, David; He, Rui; Burch, Kenneth S.; Henriksen, Erik A.
Abstract: We present Raman spectroscopy experiments on exfoliated α -RuCl3, from tens of nm thick down to single layers. Besides unexpectedly finding this material to be air stable, in the thinnest layers we observe the appearance with decreasing temperature of a symmetry-forbidden mode in crossed polarization, along with an anomalous broadening of a mode at 164 cm −1 that is known to couple to a continuum of magnetic excitations. This may be due to an enhancement of magnetic fluctuations and evidence for a distorted honeycomb lattice in single- and bilayer samples. Highlights: α-RuCl3, a layered candidate material to host the Kitaev quantum spin liquid, is exfoliated down to single- and few-layer flakes. Raman spectroscopy is performed to study the evolution of structure with thickness and temperature. A symmetry-forbidden mode appears in only the thinnest flakes at low temperature, evidencing a possible structural transformation. Phonon width and energy of a mode sensitive to magnetic fluctuations shows a strong temperature dependence in contrast to bulk material.